Treatment of cerebrospinal fluid leakage with prolonged use of subfascial epidural drain and antibiotics in patients of thoracic myelopathy after posterior decompression surgery - Zhai, Jiliang; Guo, Shigong; He, Da; Zhao, Yu (Frontiers in Surgery, 2023)
Background: Cerebrospinal fluid leakage (CSFL) is a prevalent and vexing complication associated with spine surgery. No standard protocol is available guiding CSFL management, especially for thoracic CSFL.The aim of this study was to retrospectively evaluate the efficacy of prolonged use of subfascial epidural drain and antibiotics to treat CSFL after posterior thoracic decompression surgery.Methods: 56 patients with an average age of 52.3 years (24 to 76 years), who underwent thoracic decompression with CSFL (group A) and 65 patients with an average age of 54.9 years (25 to 80 years) without CSFL (group B) were retrospectively reviewed. Patients in group A had prolonged use of subfascial drainage and antibiotics and patients in group B were treated with conventional methods. The surgical results and rate of wound related complications was compared between the two groups.The average subfascial drainage time was 7.0±2.7 days (2 to 16 days) and 3.8±1.4 days (2 to 7 days) in group A and B, respectively. Higher occupation rate (>49%), presence of dural ossification and higher MRI grade (>2) were more likely to presented with CSFL. In group A, four patients (7.1%) presented with deep wound infection and were successfully managed with wound debridement or intravenous antibiotics. In group B, one patient (1.5%) had a superficial wound infection and was treated with antibiotics. No patients presented with wound dehiscence, wound exudation or CSF fistulation.The occupation rate of ossified mass and presence of dural ossification 3 were the major risk factors of CSFL. No significant difference in infection rates was observed between the patients in group A and B.